Synchronous or Metachronous Hairy Cell Leukemia and Chronic Lymphocytic Leukemia: A Case Series and Literature Review - Verma, Vivek (Front Oncol, 2017)
INTRODUCTION: Concurrent hairy cell leukemia (HCL) and chronic lymphocytic leukemia (CLL) is rare; management is inadequately described in the literature. METHODS: Retrospective chart review and clinical follow-up. RESULTS: Five patients are described. The first patient developed synchronous HCL and CLL and was treated with rituximab for 13 months with HCL in remission and stable CLL. The second patient developed HCL and was treated with cladribine. His disease recurred 7 years later which was retreated with cladribine. Seven years later, he developed asymptomatic CLL. The third patient developed CLL, managed expectantly, then developed HCL 10 months later, and was treated with cladribine. Although his HCL went into remission, there was a slow redevelopment of CLL for which expectant management was done. The fourth patient developed concurrent CLL and HCL, received cladribine, with subsequent development of worsening abdominal lymphadenopathy and was lost to follow-up. The last patient developed concurrent HCL and CLL and was also diagnosed with lung adenocarcinoma; this patient was also lost to follow-up. CONCLUSION: The development of concurrent HCL and CLL may indicate a common origin. Patients with HCL may subsequently develop CLL, thus mimicking a relapse of HCL. Therapy requires individualized approach including watchful waiting in asymptomatic cases. Rituximab may be useful to treat both disorders simultaneously.